THE RELATIONSHIP BETWEEN THE LEVEL OF UNDERSTANDING OF ECOLOGICAL ISLAMIC MATERIAL AND STUDENTS' ECOLOGICAL LITERACY - Abdul Afwu Godly Prayitno; Nurbaeti; Yoga Wahyu Wicaksono; Sabarudin; Topan Priananda Adinata (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Islamic Education plays a vital role not only in shaping the spiritual character of students but also in internalizing the values of environmental responsibility through the concept of Ecological Islam. This study aims to analyze the relationship between the understanding of Ecological Islam concepts and the ecological literacy of undergraduate students in addressing environmental issues. A quantitative approach with an ex post facto correlational design was employed. The research sample consisted of 219 students from the Faculty of Teacher Training and Education at Universitas PGRI Banyuwangi, selected using a stratified cluster sampling technique. Data were collected through the documentation of Islamic Education course grades to measure the understanding of Ecological Islam, alongside an adapted version of the Middle School Environmental Literacy Survey (MSELS) instrument to assess ecological literacy. Data analysis was performed using descriptive statistics and Pearson’s Product-Moment correlation. The results demonstrated that: (1) students' ecological literacy was in the moderate category (87.21% of students, = 62,20); (2) students' understanding of Ecological Islam was in the high category (67.58% of students, = 84,38); and (3) there was a significant and very strong positive relationship between the understanding of Ecological Islam and students' ecological literacy (=0,977, p(two-tailed) <0,01). These findings demonstrate that a robust theological-ecological understanding significantly contributes to enhancing environmental awareness. Consequently, lecturers and curriculum designers are encouraged to continuously and sustainably integrate global environmental issues into Islamic Education learning.